Historic train stations in Małopolskie Province during the railroad industry regression - Chaberko Tomasz (Journal for Geography, 2008)
Train stations tend to be the most representative constructions of the railroad industry. In many cases they are considered as interesting transportation and architectural monuments. In Poland, where the rail network was developed mostly before World War I, they constitute the most numerous group of monuments of Poland’s industrial era. The main goal of this paper is to indicate the historic train station buildings (those dating back to the period 1847-1918) in Małopolskie Province and determine their role in the modern railroad transportation system. As a backdrop for the discussion, a few background elements are included. They are: chosen architectural hallmarks of train stations in the Austro-Hungarian Empire, selected issues concerning the railroad history of Galicia and contemporary aspects of the railroad industry’s current regression. It is in this context that the state and prospective utilization of historic rail stations are portrayed.